(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article is devoted to the problems of creating semantic fields when expressing the semantics of lexical units in a database format, a parametric description of the meaning of a word. Database technologies are actively used in lexicographic practice. In the field of creating lexicographic databases, including the semantic description of some semantic units, it will be necessary to develop a system for automatic translation of a natural language, a machine translation system